Synchronous division and rates of macromolecular synthesis in Haemophilus influenzae competent for genetic transformation. - Scocca, J J (1978)
When competent Haemophilus influenzae were returned to complete growth medium, they resumed growth at once and underwent a synchronous division after 20 to 25 min. The rate of DNA synthesis increased to the definitive rate very quickly after resumption of growth. In contrast, the rate of RNA synthesis remained low until the time of division, at which time it accelerated dramatically. Changes in the rate of protein synthesis were similar in form to those of RNA synthesis. The kinetics of loss of competence upon resumption of growth had a pattern similar to the rate of RNA synthesis, and both processes accelerated markedly at the time of cell division, suggesting an inverse relationship between RNA synthesis and the ability to take up DNA.